1989
DOI: 10.1016/s0006-3495(89)82919-4
|View full text |Cite
|
Sign up to set email alerts
|

Low angle light scattering studies on whole, half, and quarter molecules of T2 bacteriophage DNA

Abstract: Static light scattering measurements have been made at angles as low as 8 degrees on whole, half, and quarter molecules of native, T2 bacteriophage DNA in 0.195 M Na+. The fragments were obtained by high-speed stirring of the native DNA, and fractionated on methylated-albumin-kieselguhr columns. Accompanying measurements of sedimentation coefficients and intrinsic viscosities were made. Because linear extrapolations of light scattering data above 8 degrees for these samples were suspect, the measurements were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 56 publications
3
30
0
Order By: Relevance
“…Other techniques such as static light scattering were considered, but such measurements are extremely difficult for long molecules and become virtually impossible for molecules longer than Ϸ60 m (38). Therefore, although there is no apparent way to directly measure R G for our entire range of molecular lengths, we can still examine whether our data are consistent with theories that relate R G and D. The hydrodynamic radius R H can be calculated from D by using the Stokes-Einstein relation D ϭ k B T͞6p R H , where k B is Boltzmann's constant, T is temperature (Х297 K), and is solvent viscosity (Х1.2 cPa).…”
Section: Resultsmentioning
confidence: 99%
“…Other techniques such as static light scattering were considered, but such measurements are extremely difficult for long molecules and become virtually impossible for molecules longer than Ϸ60 m (38). Therefore, although there is no apparent way to directly measure R G for our entire range of molecular lengths, we can still examine whether our data are consistent with theories that relate R G and D. The hydrodynamic radius R H can be calculated from D by using the Stokes-Einstein relation D ϭ k B T͞6p R H , where k B is Boltzmann's constant, T is temperature (Х297 K), and is solvent viscosity (Х1.2 cPa).…”
Section: Resultsmentioning
confidence: 99%
“…This potentially alters the persistence length and effective diameter of native dsDNA, and nominally increases the contour length by as much as 50% (ref. 45). Of the experimental measurements discussed in Section 1, Strychalski et al…”
Section: Fluorescent Dyesmentioning
confidence: 99%
“…In the case of the DNA studies presented here, we note the following. In some studies, the polydispersity is either not explicitly reported 44,55,56 …”
Section: Polydispersity Effectmentioning
confidence: 99%